2014
DOI: 10.1097/iae.0000000000000189
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure Elevation After Uncomplicated Pars Plana Vitrectomy

Abstract: Uncomplicated PPV seems to increase the IOP, particularly in those who are pseudophakic and have a family history of open-angle glaucoma. This increase in IOP may lead to glaucomatous damage if not managed appropriately. Patients with a previous PPV need to be followed by an ophthalmologist to monitor the IOP in the vitrectomized eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 18 publications
1
38
1
1
Order By: Relevance
“…Lens extraction has been described as a major risk factor for the development of glaucoma after uncomplicated pars plana vitrectomy [87]. Other risk factors include pseudophakia and family history of open angle glaucoma [88].
Fig.
…”
Section: Glaucoma After Retinal Surgerymentioning
confidence: 99%
“…Lens extraction has been described as a major risk factor for the development of glaucoma after uncomplicated pars plana vitrectomy [87]. Other risk factors include pseudophakia and family history of open angle glaucoma [88].
Fig.
…”
Section: Glaucoma After Retinal Surgerymentioning
confidence: 99%
“…These rates are similar to those reported by Luk et al [19], who reported an overall incidence of 7.9% (eight eyes) with a higher rate in pseudophakic (13%) compared with phakic (2%) eyes. More recently, a retrospective study by Wu et al [20▪▪] examined 198 patients who underwent PPV for idiopathic epiretinal membrane. The incidence of elevated IOP was 19.2% in vitrectomized eyes, compared with 4.5% in the unoperated fellow eye.…”
Section: Glaucoma After Pars Plana Vitrectomymentioning
confidence: 99%
“…The incidence of elevated IOP was 19.2% in vitrectomized eyes, compared with 4.5% in the unoperated fellow eye. As a result of these findings, PPV has been suggested as a risk factor for the development of secondary open-angle glaucoma [1719,20▪▪]. Other studies, however, have not found a link between open-angle glaucoma or IOP elevation and uncomplicated PPV [21,22].…”
Section: Glaucoma After Pars Plana Vitrectomymentioning
confidence: 99%
“…Consequently, vitrectomy and combined cataract extraction can triple the gradient possibly resulting in increased oxidative stress on the TM [ 14 , 15 ]. Based on these physiological considerations, several studies observed a significant elevation in long-term IOP after vitrectomy for different pathologies [ 16 21 ]. However, other studies failed to show significant changes in IOP [ 22 25 ] and some even showed reduced IOP values [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%